Techniques and graft materials for repairing peripheral nerve defects - Zou, Xiaodi; Dong, Yanzhao; Alhaskawi, Ahmad; Zhou, Haiying; Ezzi, Sohaib Hasan Abdullah; Kota, Vishnu Goutham; Abdulla, Mohamed Hasan Abdulla Hasan; Abdalbary, Sahar Ahmed; Lu, Hui; Wang, Changxin (Frontiers in Neurology, 2024)
Peripheral nerve defects refer to damage or destruction occurring in the peripheral nervous system, typically affecting the limbs and face. The current primary approaches to address peripheral nerve defects involve the utilization of autologous nerve transplants or the transplantation of artificial material. Nevertheless, these methods possess certain limitations, such as inadequate availability of donor nerve or unsatisfactory regenerative outcomes post-transplantation. Biomaterials have been extensively studied as an alternative approach to promote the repair of peripheral neve defects. These biomaterials include both natural and synthetic materials. Natural materials consist of collagen, chitosan, and silk, while synthetic materials consist of polyurethane, polylactic acid, and polycaprolactone. Recently, several new neural repair technologies have also been developed, such as nerve regeneration bridging technology, electrical stimulation technology, and stem cell therapy technology. Overall, biomaterials and new neural repair technologies provide new methods and opportunities for repairing peripheral nerve defects. However, these methods still require further research and development to enhance their effectiveness and feasibility.